Analysis of the Use of Gasing Method on the Ability to Understand Physical Concepts - Aidha Putri Azmi; Nur afiyati (International Journal of Mathematics and Science Education, 2024)
This research aims to evaluate the use of the spinning top method in improving students' ability to understand physics concepts. The spinning top method, which involves active and interactive learning through physical demonstrations, is used as an alternative approach in teaching physics. This research involved students as research subjects and was carried out by comparing learning outcomes between the group that received training using the gasing method and the control group that used the conventional method. Data was collected through physics concept understanding tests before and after the intervention, as well as through classroom observations. Data analysis was carried out to evaluate the effectiveness of the spinning top method in increasing students' understanding of physics concepts. It is hoped that the research results can provide valuable insight for educational practitioners in developing more interactive and effective learning strategies in the context of physics learning.